Time distribution of design storm rainfall over various sub-catchments of river Mahanadi - MUKHERJEE , K.; APTE, N.Y. (MAUSAM, 1990)
In estimation of design flood a basic parameter used is design storm. Design storm computation includes spatial and temporal distribution of rainfall .In the present study an attempt has been made to compare the values of time distribution of rainfall of different sub-catchments of the river Mahanadi with that of the entire catchment.